New stratigraphic constraints for the Quaternary source‐to‐sink history of the Amatrice Basin (central Apennines, Italy). (3rd November 2019) - Mancini, Marco; Vignaroli, Gianluca; Bucci, Francesco; Cardinali, Mauro; Cavinato, Gian Paolo; Di salvo, Cristina; Giallini, Silvia; Moscatelli, Massimiliano; Polpetta, Federica; Putignano, Maria Luisa; Santangelo, Michele; Sirianni, Pietro
Abstract : New stratigraphic constraints have been detailed for the Amatrice Basin, an intermountain morpho‐structural depression of the central Apennines (Italy) hosting up to 60‐m‐thick Quaternary continental deposits. Through the results coming from a 1:5, 000 scale field survey and from facies analyses, we documented the geometry, thickness, and extent of the post‐orogenic continental deposits filling this basin. The Quaternary deposits form a complex architecture of purely aggradational and aggradational/degradational terraces with a dominant component of conglomerates and gravels, at the bottom, and subordinate sands, at the top. The Quaternary deposits overlie an up to 1‐km‐thick succession of flysch sediments that accumulated in the western Laga Basin during the Miocene syn‐orogenic phases in central Apennines. The collected data are used to constrain the style and mechanisms of both syn‐orogenic (i.e., subsidence and terrigenous sedimentation in foredeep environment) and post‐orogenic (i.e., uplift, erosion, and continental sedimentation) phases documented for the central Apennines. In particular, the post‐orogenic history of the Amatrice Basin, if compared with those of surrounding intermountain basins of the central Apennines, includes limited basin subsidence, reduced thickness of the post‐orogenic covers and progressive deepening of the drainage network during the Quaternary. The results shed light on the source‐to‐sink history of the Amatrice Basin, which results from a long‐lived interaction between regional‐scale factors (climate changes, chain uplift, and extensional tectonic regime) that influenced the activity of the hydrodynamic pattern and the amount of intrabasinal sedimentation during the Quaternary.